2008
DOI: 10.1186/1757-1626-1-110
|View full text |Cite
|
Sign up to set email alerts
|

Severe hepatitis with autoimmune features following a HHV-6: a case report

Abstract: HHV-6 has been identified as the aetiologic agent of exanthem subitum in infants and an acute febrile illness in young children. HHV-6 probably remains latent in the body after the primary infection and it reactivates upon host immunosuppression in a manner similar to other human herpes viruses. Primary HHV-6 infection in adults is very rare and it is not clear whether disease manifestations are similar to those observed in children.We report the case of acute hepatitis in a 18-year-old immunocompetent woman p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 16 publications
2
23
0
3
Order By: Relevance
“…A role for HHV-6A and HHV-6B has been proposed in several autoimmune disorders, including autoimmune hemolytic anemia/neutropenia [89], autoimmune acute hepatitis [90], MS [91], scleroderma [92] and Hashimoto's thyroiditis [93], among others. Early observations documented a higher rate of viral isolation in patients with collagen vascular diseases compared with healthy subjects [94].…”
Section: Mechanisms Of Immunomodulation and Immunosuppression By Hhv-6amentioning
confidence: 99%
“…A role for HHV-6A and HHV-6B has been proposed in several autoimmune disorders, including autoimmune hemolytic anemia/neutropenia [89], autoimmune acute hepatitis [90], MS [91], scleroderma [92] and Hashimoto's thyroiditis [93], among others. Early observations documented a higher rate of viral isolation in patients with collagen vascular diseases compared with healthy subjects [94].…”
Section: Mechanisms Of Immunomodulation and Immunosuppression By Hhv-6amentioning
confidence: 99%
“…В послед-ние годы приводятся данные о поражении пече-ни, вызванные вирусами герпеса человека 6-го типа (ВГЧ-6), с возможностью развития хрони-ческого гепатита и формирования цирроза пече-ни [2,3,9,10].…”
Section: Introductionunclassified
“…Even though the pathophysiology of this disease is not well known, it has previously been suggested that viral infections may trigger the development of AIH in susceptible individuals since viral epitopes can mimic autoantigen epitopes in the liver. Indeed, several cases of AIH have been reported in patients with persistently altered liver tests after acute hepatitis A, B, C or E infection, Epstein‐Barr virus and human herpes 6 virus …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several cases of AIH have been reported in patients with persistently altered liver tests after acute hepatitis A, B, C or E infection, Epstein-Barr virus and human herpes 6 virus. [2][3][4][5] Hepatitis E virus (HEV) is a small positive-strand RNA genome with eight genotypes. Genotypes 1 and 2 cause epidemic outbreaks in developing countries, they only infect humans, and its transmission is faecal-oral.…”
Section: Introductionmentioning
confidence: 99%